Development and Psychometrics of an Interpersonal Communication Skills Scale (A.S.M.A) among Zanjan Health Volunteers - Shamsaddin Niknami; Ali Reza Hidarnia; Mohammad Masoud Vakili (Tehran University of Medical Sciences, 2012)
Background & Aim: It is crucial to assess communication skills among health workers using valid culture-based instruments. This study aimed to develop and assess psychometric properties of the Interpersonal Communication Skills Scale among Zanjan Health Volunteers. Methods & Materials: In this study, a total of 191 health volunteers participated in a self-rating assessment of the Communication Skills Scale (CSS). Moreover, 14 experts were asked to rate each item based on the relevance, clarity, and simplicity. Through a literature review, we developed an instrument with 43 items. The validity of the instrument was determined using the impact item method, content validity ratio (CVR), content validity index (CVI), face validity and exploratory factor analysis. Reliability of the instrument was reported by Alpha Cronbach coefficient. The CSS finally contained 35 items, divided into two categories: general and specific communication skills. Results: Of 43 items, those with impact item index over 1.5, CVR over 0.51, and CVI over 0.79 were considered as valid; while the rest were discarded resulting in a 35-item scale. Factor analysis was carried out to determine the relationship among the items of the CSS. Exploratory factor analysis reduced the list of items to 30, which were divided into seven groups with a minimum eigenvalue of 1 for each factor, capable of predicting 68.8% of the variance. Internal reliability of the scale was determined by alpha Cronbach coefficient (0.91). Conclusion: The results of this study indicated that the CSS is a valid and reliable instrument for assessment of the communication skills among health volunteers in Zanjan. These findings could be used for developing similar instruments in other health worker groups.